Nutrient Digestibility, N Balance, Performance, and Blood Parameters of Kacang Goats Differing in GDF9 Genotype Fed Different Sources of Dietary Fiber - Irawan, A.; Hartatik , T.; Bintara, S.; Astuti, A.; Kustantinah (Tropical Animal Science Journal, 2024)
This study aims to determine the impact of different GDF9 genotypes on feed intake, nutrient digestibility, and nitrogen balance in Kacang goats by examining various metabolic processes. Twenty-nine Kacang goats were genotyped using PCR-RFLP DNA at position g.3855A/C of the GDF9 gene in exon 2. A 2 × 2 factorial design with two factors, namely, diet type (diets 1 and 2) and genotype (homozygote AA and heterozygote AC), was adopted. Diet 1 group comprised 11 goats with the AA genotype and 4 goats with the AC genotype, and the diet 2 group consisted of 9 goats with the AA genotype and 5 goats with the AC genotype. Both diets had the same protein content (iso-protein) and consisted of free-choice Napier grass (Pennisetum purpureum). Diet 1 had an additional 400 g of concentrate containing 11.25% crude protein (CP) and 55.86% total digestible nutrients (TDN). Diet 2 was a total mixed ration (TMR) containing 12.46% crude protein and 67.92% TDN. Results demonstrated a significant interaction (pC can be used for genomic marker selection of high-quality Kacang goats in nutrient digestibility.